Deaths related to nitrogen inhalation: Analytical challenges. (December 2020) - Giorgetti, Arianna; Pelletti, Guido; Barone, Rossella; Garagnani, Marco; Rossi, Francesca; Guadagnini, Gianni; Fais, Paolo; Pelotti, Susi
Highlights: Toxicological analyses for Nitrogen ( N2 ) are rarely performed in fatal N2 inhalation. A literature review of cases of fatal N2 inhalation is reported. We applied two methods for the identification of an excess of N2 in a real case. Both methods can be applied with instrumentation normally available in laboratories. Abstract: Dinitrogen ( N2 ) has been increasingly connected to suicidal deaths. The analysis of N2 in post-mortem cases still represents a major challenge in forensic toxicology and circumstantial data has so far played a major role for the determination of the cause of death. In this paper, after presenting a review of cases of N2 intoxication described in forensic literature, we report the application of two approaches in order to quantify an excess of N2 in post-mortem whole blood collected from a case of suicide by nitrogen inhalation. N2 analyses were performed by GC–MS on the suicidal case and on controls taken from 10 autopsy cases with similar PMI (5 traumatic deaths and 5 deaths by asphyxia). The percentage of N2 was estimated by building a five-point N2 peak area calibration curve (0, 15.6 %, 62.4 % 78.1 %, 100 %) and through an external QC, assessing linearity, accuracy and precision, LLOQ, specificity and stability of N2 in the sample vial. Percentage of N2 of the case was significantly higher than the post-mortem controls (p < 0.05). The N2 /O2 ratio of the case and controls was also calculated as an additional indicator, and was significantly higher in the case (p < 0.05). The strengths and the limitation of both methods are reported in the paper. Toxicological confirmation for N2 are rarely performed when the cause of death is evident, probably due to the lack of validated methods and the complexity of the interpretation of N2 concentration in biological fluids. The presented methods can be rapidly and profitably applied with instrumentation normally available in forensic laboratories.